Restudy of Conception of “House” in Islam: An Approach to Describe Functional Aspects of House According to Verses of Holy Quran - Azemati, Saeed; Harchegani, Ali Kiyani; Torki, Leila; Dehkordi, Seyed Saleh Rokni; Pour, Elham Mosa (Journal of History Culture and Art Research, 2017)
Abstract Islam specified some rules for supplying real needs of human communities so that the human beings may live together with upmost security and health far from the concerns and problems by observing such principles, and one of the most important endowments pointed by the Quran is human’s place of residence. Conception of house in Islam is a subject studied in this paper. House, in fact, is one of the most important human requirements, and Muslims shall live under conditions and based on the religious values that they may worship God and provide the immortal life. The religious teachings in human life -lead the men to have a special imagination- based on the functional and aesthetic values are defined. Architecture and house construction are a field for the creation and description of human religious beliefs, and also a criterion for evaluation of meeting the said values. The purpose of this paper is to express necessary recognition of the principles and philosophy of verses of Holy Quran in terms of the house and shelter, and also its compliance with the social, cultural and functional structure in designing architectural buildings. Therefore, the verses of the Holy Quran are used in this research as the source of the principles and fundamentals of Islamic thinking and ontology in explaining the functional dimensions of house by enjoying the analytical-descriptive methodology.